LABORATORY RESEARCHES ON EFFICIENCY EVALUATION OF WELL SCREEN REGENERATION - V. V. Ivashechkin; A. M. Kondratovich; A. N. Sheiko; V. V. Gubin (Наука и техника)
Results pertaining to efficiency evaluation of well screen regeneration using a combined impulse and reagent method is given in the paper. In order to ensure complete cleaning of screen fragment from sedimentation a gas and dynamic set without and with pneumatic packers has been applied. After  gas and dynamic regeneration a part of the screen with sedimentation has been subjected to a reagent treatment while using hydrochloric acid and «Descam» reagent.The combined method for well screen regeneration is considered as the most efficient one and this fact is proved by laboratory experiments.